PEMODELAN DAN SIMULASI TOPOLOGI SINGLE ENDED PRIMARY INDUCTOR CONVERTER (SEPIC) UNTUK MINI 3 PLUS WIND TURBINE - Ryan Prasetiyo; Dwindra Wilham Maulana; Camellia Panatarani; I Made Joni (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
In order to have a DC-DC buck boost converter with performances as desired specifications, the design process was performed by developing a model and simulation. The purpose of this research was to design a converter applied for a MINI 3 plus Wind Turbine. The converter topology was designed with Single Ended Primary Inductor Converter (SEPIC) using  a Continuous Conduction Mode (CCM). The output specifications of converter are input voltage 60 V, input current 7,5 A, output voltage 25 V, output current 4,17 A, and frequency 25kHz. The average state space method was used to obtain its transfer function. The transfer function represented the characteristics of an average state of SEPIC converter system. The characteristics and designed quality of SEPIC converter determined by system performance analysis. The results showed that as designed SEPIC converter achieved excellent performances and stability based on their overshoot, rise time, settling time, frequency, and location of pole-zeros.  Incontrast, the designed SEPIC converter showed that converter increased the input voltage (boost mode) with duty cycle more than 50% and reduced voltage (buck mode) with duty cycle less than 50%. It was concluded that the designed converter system achieved excellent and stable performances.Keywords: SEPIC converter, state space analysis, transfer function, DC-DC converter.